A simplified model to evaluate noise reduction interventions in the urban environment. Issue 1 (March 2016) - Magrini, Anna; Lisot, Aline
Traffic noise is a major problem in all large cities. The surface acoustical characteristics (e.g. referred to roads, pedestrian traffic areas, building façades, building surfaces, in general) affect the noise propagation in the urban environment. Through a better outdoor design and management (e.g. by means of green areas, porous asphalt, speed control), or building refurbishment actions (acoustic plaster, absorbing shading devices), the increasing of surface absorption could be useful to mitigate noise environmental pollution, and therefore to reduce the sound levels in the proximity of the building façades for their entire height. The reduction of the noise levels outside the buildings would determine lower indoor noise levels, and therefore a better situation, without direct actions on the building walls. Through a series of noise propagation calculations in urban environments, by means of a three-dimensional simulation model, the influence of some configurations and the potential impact of some intervention solutions are quantified. In the first stage of the research, the analysis of a simplified model is conducted, to evaluate the influence of noise on the building façades, based on a simplified geometry of the urban environment and of the surface acoustic features. The same analysis is validated by means of a more detailed model, corresponding to the configuration of an existing built area, to verify if the analyses performed by means of the simplified model can be extended to more complex layouts. Successively, calculations are developed to quantify the noise levels that occur with different acoustic (absorption of façades, soil, asphalt, or green elements) and geometric (road width, buildings height, presence of balconies, etc.) characteristics to show the potential reduction given by some interventions. Solutions that can lead to a more significant reduction of the noise in correspondence of the façades are then summarized. The simplified geometrical model appears to be suitable for preliminary investigations as the maximum error found for narrower roads is equal to 17%.